Odpowiedź :
Odpowiedź:
a) - (3a-4b +c ) - (3a+b-2c) = -3a+4b-c-3a-b+2c= -6a+3b+c
b) 7 - (z+2y-3z) + (2x-3y-5z -3) =7-z-2y+3z+2x-3y-5z-3= 2x-5y-3z+4
c)-3ab+(-2ab-4b-c)+3c-6x - (-x+7x-3zc) =-3ab-2ab-4b-c+3c-6x+x-7x+3zc=-5ab-4b+2c-12x+3zc
d)7x – 8 – (5x + 6 ) = 7x-8-5x-6=2x-14
e) – ( - 5c – 8 ) + ( 6 – 9c ) = 5c+8+6-9c=-4c+14
f) 4x + (x - 5) – 8x – (-3x+8) + 10 – 12x =4x+x-5-8x+3x-8+10-12x=-12x-3
Zadanie
a)
- (3a - 4b +c ) - (3a + b - 2c) = -3a + 4b - c - 3a - b + 2c = -6a + 3b + c
b)
7 - (z + 2y - 3z) + (2x - 3y - 5z - 3) = 7 - 2y + 2z + 2x - 3y - 5z - 3 =
= 2x - 5y - 3z + 4
c)
-3ab + (-2ab - 4b - c) + 3c - 6x - (-x + 7x - 3zc) =
= -3ab - 2ab - 4b - c + 3c - 6x + x - 7x + 3zc = -5ab - 4b + 2c - 12x + 3zc
d)
7x - 8 - (5x + 6 ) = 7x - 8 - 5x - 6 = 2x - 14
e)
- (- 5c - 8 ) + ( 6 - 9c ) = 5c + 8 + 6 - 9c = -4c + 14
f)
4x + (x - 5) - 8x - (-3x + 8) + 10 - 12x = 4x + x - 5 - 8x + 3x - 8 + 10 - 12x =
= -12x - 3